Physical activity promotion and adults with intellectual disabilities: A neglected area. (June 2022) - MacDonald, Cathy; Bush, Paula L; Foley, John T
Background: The objective was to review physical activity (PA) promotion interventions among individuals with intellectual disability and provide recommendations for increasing PA. Methods: A systematic mapping review was conducted in which physical activity intervention studies for adults with a disability were identified, selected, and appraised. Data were extracted regarding the study design, results, and authors' recommendations. Data were analyzed using a social-ecological framework. Results: A comprehensive search of the peer reviewed literature yielded 5 studies (3 quantitative, 1 mixed methods, and 1 pre-post delayed). Studies used physical activity promotion strategies at the intrapersonal, interpersonal, organizational, community, and policy levels have been used to date. Conclusions: Recommendations are presented for researchers and practitioners seeking to increase the level of PA of adults with intellectual disability.